A rare intersection: squamous cell carcinoma of the tonsil and the anti-TIF1 syndrome masquerade - Manush Sondhi; Megan Lear; Saleha Dar; Madiha Tariq (BMC Rheumatology)
Abstract Background Dermatomyositis is a chronic inflammatory condition affecting muscles and skin, often associated with an increased risk of cancer. Specific autoantibodies, including anti-TIF1 (Transcription Intermediary Factor 1), have been linked to this risk. We present a case of dermatomyositis in a male patient positive for anti-TIF1 antibodies, subsequently diagnosed with squamous cell carcinoma of the tonsil, a novel association not previously documented. Early recognition of such associations is crucial for timely intervention and improved outcomes in these patients. Case presentation A 53-year-old Caucasian male with hyperlipidemia presented with chronic dry, scaly skin and pruritus, diagnosed with eczematous dermatitis. Despite treatment, symptoms persisted. After two years, he reported increased redness of the rash and new eruptions on his hands and fingers. During a rheumatology visit, he reported weight loss, fatigue, muscle weakness, and trismus. Further evaluation indicated signs of dermatomyositis, and laboratory tests revealed anti-TIF1 antibodies, prompting further investigation. The patient underwent age-appropriate cancer screening, and due to a known association with malignancy, a positron emission scan was ordered, detecting increased activity in the right tonsil. Subsequent magnetic resonance imaging showed a suspicious mass in the tonsillar area. A biopsy confirmed invasive squamous cell carcinoma positive for P16+. Initial treatment included radiotherapy, with a post-treatment PET scan showing no evidence of disease. However, four months later, the cancer recurred, leading to significant symptoms and complications. Despite supportive measures, the patient succumbed to high-volume oral cavity bleeding during hospitalization. Conclusions TIF1 dermatomyositis is a unique subset of dermatomyositis with a strong association with malignancy, particularly squamous cell carcinoma (SCC). Mechanisms connecting TIF1 dermatomyositis and cancer involve gene expression dysregulation and chronic inflammation. Anti-TIF1 antibodies are key biomarkers, with IgG2 isotype levels highly predictive of cancer risk. Common malignancies include ovarian, breast, and lung cancers, often detected within three years of dermatomyositis onset. Distinctive features include severe skin lesions, dysphagia, and minimal interstitial lung disease. Management focuses on early cancer detection and treatment, with options for refractory disease, including IVIg, rituximab, and emerging therapies like JAK inhibitors. Our case highlights a new association between TIF1α antibodies and tonsil squamous cell carcinoma. Despite successful radiotherapy, cancer recurred. TIF1 antibody detection should prompt rigorous cancer screening, emphasizing multidisciplinary management.